Analysis of Women Participation in Piggery Production in Rivers State, Nigeria - Odinwa, A. B.; Amugo, N. M. (Research Highlights in Agricultural Sciences Vol. 1, 2022)
The study focused on women participation in piggery production in Rivers State. The purpose was to: describe the social-economic characteristics of women participating in piggery production; establish the level at which women participate in piggery production; and scrutinize the constraints to women participation in piggery production in the study area. Descriptive survey design was adopted to observe a cross section of women in piggery production in Rivers State. Both simple random and snowball sampling techniques were used to select 3 LGAs, 18 communities and 72 women for the study. Interview schedules and questionnaire instrument designed in Likert type rating scales were used to source information from the respondents. Descriptive statistics such as percentage, arithmetic mean and weighted mean scores were used to analyze the data. Simple Regression and Analysis of variance (ANOVA) were the inferential statistics used to test the stated hypotheses of the study at 0.05% significant level. The result showed 36 years old as the mean age of the women in piggery production in the study area and that majority of them were married (68%) and with a mean household size of six (6) persons per family. It showed a mean annual income of (N232,291.00) only from piggery production. Regression result showed that nature of farming, annual income and household size with t-values of (1.430*), (1.254*) and (1.233*) respectively, had positive effect on women participation in piggery production at 5% significant level. It also indicates that women participation in piggery production in the area were very low (CM = 2.11) but differed significantly among the three LGAs in favour of Oyigbo LGA (CM = 2.56). Finally, the result showed that: insecurity challenges (GM = 3.30), price fluctuations of pig products (GM = 3.24), inadequate credit (GM = 3.17), land ownership issues (GM = 3.16), poor storage facilities (GM = 3.09), pest and disease problems (GM = 3.06) among other challenges, posed very serious constraints to women participation in piggery production in the study area. Based on the findings, the study recommended among others that: Rivers women should be encouraged by government and non-governmental organizations to actively participate in piggery production through grants and subsidies; Extension agencies in the State should register more women and develop special extension package for piggery production in all the LGAs of Rivers State; and Agricultural credits institutions in the State should give priority attention to women in livestock and pig production in particular in Rivers State.